Bond strengths, degree of conversion of the cement and molecular structure of the adhesive-dentine joint in fibre post restorations - de Melo, Renata Marques [UNESP]; Bottino, Marco Antonio [UNESP]; Harrop Galvao, Roberto Kawakami; Soboyejo, Winston O. (Elsevier B.V., 2012)
Objectives: Because fibre post restorations are influenced by multiple factors such as the types of bonding materials, the dentine region and the time under moist exposure, this study sought to determine the bond strength of endodontic restorations and its relation to the degree of conversion of the cement layer and the molecular structure of the dentine-bonded joints.Methods: The performance of 2 etch-and-rinse (All-Bond 2 and One-Step Plus) and 2 self-etch (Clearfil SE Bond and Xeno III) adhesives at post spaces regions, after 7 d or 4 m, was evaluated. FRC Postec Plus posts were cemented to the root canal with a dual-cure resin cement (Duo-Link). Transverse sections of the tooth were subjected to push-out testing, to degree-of-conversion measurements and to hybrid layer evaluation through mu-Raman spectroscopy.Results: Coronal bonding was higher than cervical and middle bonding. The hybrid layer was thicker for the etch-and-rinse systems, with thicknesses decreasing towards the middle region. The degree of conversion measured for the 3-step etch-and-rinse group after 4 m was significantly higher than that for the self-etching groups.Conclusions: Although not totally stable at the adhesive-dentine interface, the 3-step etch-and-rinse adhesive in the coronal dentine provided the best bond strength, degree of conversion of the cement and hybrid layer thickness in post restorations, in both short- and long-term analyses. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Bonding agents; Root canal dentine; Fibre posts; Degree of conversion; Raman spectroscopy